British and unaccompanied asylum-seeking children in the care of the local authority who go missing - Bassey, Amanda (2021)
This thesis plans to add to the limited research into the increasing problem of children under the care of the local authority in United Kingdom running away and/or being reported missing. Specifically, to understand the factors that increase the likelihood of this sample group going missing. Whether this group of children, which can also include Unaccompanied Asylum-Seeking Children (UASC) are heterogeneous or homogeneous in their characteristics, and the differences if found to be heterogeneous. To explore validated risk assessments in use, and to see whether current governmental statutes are being followed with regards to missing and/or runaway children under the care of the local authority.